Concordance of bacterial communities of two tick species and blood of their shared rodent host. Issue 10 (22nd April 2015) - Rynkiewicz, Evelyn C.; Hemmerich, Chris; Rusch, Douglas B.; Fuqua, Clay; Clay, Keith
Abstract: High‐throughput sequencing is revealing that most macro‐organisms house diverse microbial communities. Of particular interest are disease vectors whose microbiome could potentially affect pathogen transmission and vector competence. We investigated bacterial community composition and diversity of the ticks Dermacentor variabilis ( n = 68) and Ixodes scapularis ( n = 15) and blood of their shared rodent host, Peromyscus leucopus ( n = 45) to quantify bacterial diversity and concordance. The 16S rRNA gene was amplified from genomic DNA from field‐collected tick and rodent blood samples, and 454 pyrosequencing was used to elucidate their bacterial communities. After quality control, over 300 000 sequences were obtained and classified into 118 operational taxonomic units (OTUs, clustered at 97% similarity). Analysis of rarefied communities revealed that the most abundant OTUs were tick species‐specific endosymbionts, Francisella and Rickettsia, and the commonly flea‐associated bacterium Bartonella in rodent blood. An Arsenophonus and additional Francisella endosymbiont were also present in D. variabilis samples. Rickettsia was found in both tick species but not in rodent blood, suggesting that it is not transmitted during feeding. Bartonella was present in larvae and nymphs of both tick species, even those scored as unengorged. Relatively, few OTUs (e.g. Bartonella, Lactobacillus ) were found in all sample types. Overall, bacterial communities from each sample type were significantly different and highly structured, independent of their dominant OTUs. Our results point to complex microbial assemblages inhabiting ticks and host blood including infectious agents, tick‐specific endosymbionts and environmental bacteria that could potentially affect arthropod‐vectored disease dynamics.